2022
DOI: 10.3390/su142214782
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric Anomalies Associated with the 2021 Mw 7.2 Haiti Earthquake Using Machine Learning from Multiple Satellites

Abstract: The remote sensing-based Earth satellites has become a beneficial instrument for the monitoring of natural hazards. This study includes a multi-sensors analysis to estimate the spatial-temporal variations of atmospheric parameters as precursory signals to the Mw 7.2 Haiti Earthquake (EQ). We studied EQ anomalies in Land Surface Temperature (LST), Air Temperature (AT), Relative Humidity (RH), Air Pressure (AP), and Outgoing Longwave Radiation (OLR). Moreover, we found EQ-associated atmospheric abnormalities in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 80 publications
2
19
0
Order By: Relevance
“…All the satellite and ground data showed significant storm-time variations in different phases [75][76][77][78][79]. These satellite data also showed variations in the lower ionosphere [80][81][82][83][84][85]. In this study, clear EEJ enhancement has been observed at the beginning of both the 2015 and 2018 storms.…”
Section: Discussionsupporting
confidence: 58%
“…All the satellite and ground data showed significant storm-time variations in different phases [75][76][77][78][79]. These satellite data also showed variations in the lower ionosphere [80][81][82][83][84][85]. In this study, clear EEJ enhancement has been observed at the beginning of both the 2015 and 2018 storms.…”
Section: Discussionsupporting
confidence: 58%
“…The value is the absolute one and not the exceedance of the threshold. Comparing the results of this work with previous ones [57,59,60], it is possible to confirm the presence of sparse anomalies in the last weeks and days before the earthquake, but it is possible to depict more interesting periods with higher anticipation time not investigated in previous work. This is not surprising, considering that a single fault's seismic recharge time could be hundreds or thousands of years [106].…”
Section: Figure 18supporting
confidence: 57%
“…He identified an increase in anomalies in the last 20 days before the earthquake, similar to the result of the recent catastrophic earthquake in Turkey [58]. Another work by Khan et al [59] used a machine learning technique to analyse satellite atmospheric data 30 days before and up to 15 days after the mainshock. They identified an anomaly increase ten days before the mainshock.…”
Section: Introductionmentioning
confidence: 88%
“…Many of these studies focused on satellite data, because remote sensing offers distinct advantages over traditional approaches based on ground stations including global coverage and high spatial-temporal resolution [37]. Earthquake precursors derived from space-based observations, therefore, provided excellent insights into preseismic anomalies over epicentral regions [38]. Many scholars reported persistent and simultaneous anomalies in different observable parameters prior to major earthquakes [39].…”
Section: Introductionmentioning
confidence: 99%